Thrombolysis of Postoperative Acute Pulmonary Embolism with a Thrombus in Transit - Cynthia Mardinger; Paul J. E. Boiteau; John B. Kortbeek (Case Reports in Medicine)
Right heart thrombus in transit clot (RHTT) associated with a pulmonary thromboembolism (PTE) is a rare but potentially fatal diagnosis. Early diagnosis and immediate intervention are crucial. This report describes the case of a healthy, physically active 32-year-old female who presented 19 days postoperatively, following an anterior cruciate ligament reconstruction and partial lateral meniscectomy with a saddle PE, RHTT, and right ventricular (RV) strain. The patient received half of the standard dose of intravenous tissue plasminogen activator (TPA) in combination with anticoagulation and survived. Case reports of RHTT will inform future studies designed to evaluate whether and when thrombolysis should be administered.